2012
DOI: 10.1021/jp2102918
|View full text |Cite
|
Sign up to set email alerts
|

Doping Mechanism and Electronic Structure of Alkali Metal Doped Tris(8-hydroxyquinoline) Aluminum

Abstract: We investigated the electronic structures of alkali metal doped Alq3 molecules prepared by codeposition of Na and tris(8-hydroxyquinolinato)aluminum (Alq3) (Na:Alq3) using in situ synchrotron radiation photoelectron spectroscopy. The doping ratio of Na to Alq3 (R Na) was 0, 0.3, 0.6, 0.8, 2.7, 3.4, or 3.9. The work function, calculated from photoemission spectra, remained at 3.6 eV ± 0.03 eV for all samples, while the energy of the highest occupied molecular orbital increased from 2.2 to 2.85 eV as the doping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…For example, it was shown that OSCs doped with transition metals are able to display room temperature ferromagnetism due to bound magnetic polarons 5 . In turn, doping via intercalation of alkali metals has proven to be one of the most efficient methods to overcome the inherent limitations of pure OSCs: to decrease the barrier height for carrier injection at interfaces in OLEDs, to enhance the electron conductivity of materials; and, therefore, to improve the performance of the devices 9 10 11 12 . Both pure and metal-doped structures have been studied comprehensively using, inter alia , photoemission spectroscopy 13 , and for most structures either charge transfer or chemical interaction between the metal and the substrate were reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it was shown that OSCs doped with transition metals are able to display room temperature ferromagnetism due to bound magnetic polarons 5 . In turn, doping via intercalation of alkali metals has proven to be one of the most efficient methods to overcome the inherent limitations of pure OSCs: to decrease the barrier height for carrier injection at interfaces in OLEDs, to enhance the electron conductivity of materials; and, therefore, to improve the performance of the devices 9 10 11 12 . Both pure and metal-doped structures have been studied comprehensively using, inter alia , photoemission spectroscopy 13 , and for most structures either charge transfer or chemical interaction between the metal and the substrate were reported.…”
mentioning
confidence: 99%
“…Representatives of another group of OSCs, namely non-planar organic molecules with a high degree of symmetry (e.g. a PTCDA derivative, DiMe-PTCDI 15 , and Tris(8-hydroxyquinolinato)aluminium (Alq 3 ) 12 16 17 ) have been a subject of numerous studies as well. In contrast, information on the possibility to form ordered systems based on non-planar molecular OSCs with low symmetry in UHV, as well as on their doping with alkali metals remains scarce, although from the chemical and electronic viewpoints such systems are of particular interest, as specified below.…”
mentioning
confidence: 99%
“…It is well known that the Na-doped Alq 3 molecule is not a simple charge transfer complex, but a new type of organo-metallic complex. [14,19] Upon Na doping, the negative charge will be transferred to the Alq 3 molecule from the Na atom. This charge transfer and the appearance of the Na atom in the Alq 3 :Na complex make the bond lengths of the Alq 3 molecule change differently.…”
Section: -2mentioning
confidence: 99%
“…An alkali-doped Alq 3 system is an ideal representative model to analyze the evolution of electronic structure through interaction between metals and organic materials and also has been studied generally in organic light-emitting diodes. [16,17] Furthermore, Johansson et al [18] used a combination of x-ray and ultraviolet photoemission spectroscopy as well as density functional theory (DFT) calculations to discuss the interaction of Alq 3 with alkali metals Li and K. Kim et al [19] discussed the doping mechanism and electronic structure of alkali metal Na-doped Alq 3 , they found that there is a monotonic shift of the lowest unoccupied molecular orbital (LUMO) toward the Fermi level with the increasing Na-doping concentration.…”
mentioning
confidence: 99%
“…Many researchers have proposed the use of hybrid (organometallic/inorganic) composites to overcome these issues. Besides, those hybrids showed significant improvements in mechanical strength, thermal stability, luminescent efficiency, and charge mobility when compared to pure Alq3 [ 15 , 16 ]. Cuba et al [ 17 ] showed that Alq3-ZnO composites exhibited enhanced luminescence properties and a slight shift from green emission to greenish blue.…”
Section: Introductionmentioning
confidence: 99%